The causal effects of exports on firm size and labor productivity: First evidence from a matching approach - Joachim Wagner (Hamburg Institute of International Economics (HWWA), 2001)
This paper uses a large plant level panel data set from Germany and a matching approach to look for causal effects of starting to export on plant performance. We find positive effects on growth of employment, labor productivity, and wages. – – Dieses Diskussionspapier untersucht, welche Effekte der Exportstart auf die Performance von Betrieben hat. Es legt einen Matching-Ansatz zugrunde. Datenbasis ist ein großes deutsches Betriebspanel. Es werden positive Auswirkungen des Exportstarts auf Beschäftigung, Arbeitsproduktivität und Löhne nachgewiesen.
Keywords: D21; L60; F10; 330; Exports; causal effects; firm performance; matching approach; Export; Internationales Marketing; Unternehmensentwicklung; Betriebsgröße; Arbeitsproduktivität; Lohn; Beschäftigungseffekt; Deutschland